Mantle source evolution along the South Atlantic Transect (31?S) records a transition from HIMU plume component to depleted MORB - Kempton, Pamela; Coggon, R. M.; Millar, I.; Belgrano, T. M.; Albers, E.; Michalik, A.; Milton, A.; Evans, A. D.; Taylor, R. N.; Teagle, D. A. H. (My University, 2025)
Interactions between mantle plumes and mid-ocean ridges create considerable spatial variation in composition along ridge axes. What is less well known is the temporal variation in MORB compositions along single mantle flow lines. IODP Expeditions 390/393/390C/395E recovered basaltic basement from seven sites along such a flow line, the South Atlantic Transect (SAT), on the western flank of the Mid-Atlantic Ridge at ~ 31oS. SAT basalts ?49 Ma are tholeiitic with isotopic compositions similar to MORBs from the Mid-Atlantic Ridge between 25oS 28oS. Basement from the oldest SAT site (U1556; 61.2 Ma) is more complex, consisting of three stratigraphic sequences (SSA, SSB and SSC) ranging from MORB-like at the bottom (SSC) to Ocean Island Basalt (OIB)-like at the top (SSA); their isotopic compositions are distinct relative to both younger SAT basalts and the EM1-type Tristan Gough plume that dominates the region, being more akin to HIMU. The presence of previously unrecognized HIMU mantle in this region is due to one or more ridge jumps that occurred west of the Walvis Ridge at ~65 Ma. These ridge jumps relocated the spreading axis over a portion of the HIMU plume that had previously given rise to late-stage, off-axis HIMU magmatism adjacent to the Walvis Ridge. Upwelling beneath the spreading center progressively tapped a variably depleted source, reproducing it in reverse in the volcanic stratigraphy at Site U1556. Continued upwelling beneath the spreading center removed most of the HIMU plume material within ~12 Myr, the time of Site U1558 (49.2 Ma).